2016
DOI: 10.3892/etm.2016.3748
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of human umbilical cord-derived mesenchymal stem cells for treatment of systolic heart failure

Abstract: Congestive heart failure (HF) is a leading cause of morbidity and mortality worldwide. Although advances in medical therapy, mechanical support and heart transplantation have been made, almost half of all patients with HF succumb to the disease within five years of the initial diagnosis. Therefore, treatment methods need to be identified to restore the structure and function of cardiac muscle. Three patients with HF caused by ischemic cardiomyopathy received human umbilical cord-derived mesenchymal stem cell (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…MSCs can be obtained from a variety of tissues, including the umbilical cord [52], adipose tissue [53], dental pulp [54], and bone marrow [55]. In the current study, we successfully isolated adherent cells with MSC characteristics from human Wharton’s jelly [52, 56–58]. These cells had fibroblast-like morphology, expressed mesenchymal but not hematopoietic surface markers, and effectively differentiated into adipogenic and chondrogenic lineages (Additional file 1: Figure S1).…”
Section: Discussionmentioning
confidence: 99%
“…MSCs can be obtained from a variety of tissues, including the umbilical cord [52], adipose tissue [53], dental pulp [54], and bone marrow [55]. In the current study, we successfully isolated adherent cells with MSC characteristics from human Wharton’s jelly [52, 56–58]. These cells had fibroblast-like morphology, expressed mesenchymal but not hematopoietic surface markers, and effectively differentiated into adipogenic and chondrogenic lineages (Additional file 1: Figure S1).…”
Section: Discussionmentioning
confidence: 99%
“…These cells promote cardiac tissue regeneration and angiogenesis, inhibit inflammation [ 61 ], and significantly reduce infarct size and mortality. Also, transplantation of HUC-MSCs improves the New York Heart Association functional class and the results of the Minnesota Living with Heart Failure Questionnaire and 6-min walk test, significantly improving patients’ quality of life [ 62 , 63 ]. The mechanism of HUC-MSCs’ effects on the heart is not fully understood yet, but previous studies documented that HUC-MSCs can have an anti-apoptotic function by increasing the expression of anti-apoptotic protein Bcl-2 and decreasing the expression of pro-apoptotic proteins Bax and pro-caspase-9 [ 64 ].…”
Section: Main Textmentioning
confidence: 99%
“…In this manner, the transplanted cells enhance the local contractile function of the myocardium, reduce the necrotic infracted area, and increase ejection fraction. The long-term follow-up found that the induction of blood vessel formation was also an essential part of heart repair after injury [ 63 , 64 ]. Importantly, HUC-MSCs can secrete HGF to exert anti-inflammatory effects [ 62 ].…”
Section: Main Textmentioning
confidence: 99%
“…Based on these encouraging results, the use of umbilical cord-derived stem cells was also tested in humans to develop a possible new clinical application for cardiac regeneration. The main scope of these trials was first the safety of the allogeneic transplant of the UC-MSCs: interestingly, no severe adverse effects were observed [ 133 , 134 , 135 ]. Then, four clinical trials included a control group in order to assess a potential therapeutic effect of the UC-MSCs ( Table 7 ).…”
Section: Cell Therapymentioning
confidence: 99%